Influence of integrated marketing communication tools upon consumers’ buying decisions in the context of sustainability - Batraga, Anda; Skiltere, Daina; Salkovska, Jelena; Bormane, Santa; Legzdina, Aija (University of Latvia, 2019)
A topical business subject of nowadays is the influence of integrated marketing communications (IMC) for sustainability upon various consumer audiences and their buying decisions. From the standpoint of businesses the use of integrated marketing communications in product promotion contributes to the consumption of sustainable, ecological products and, consequently, a healthy lifestyle, yet the factors influencing buyer’s buying decisions still remain topical. In this research the authors surveyed buyers of Latvian food retail chains to find out the influence of promotion-related integrated marketing communication tools for sustainability upon buyers’ buying decisions. The research brings conclusions regarding a customer-oriented approach to the processes of integrated marketing communication for sustainability, incl. the making of integrated marketing communication for sustainability to increase consumer awareness of sustainability. Purpose of the article: The purpose of the research was to study and assess the influence of promotion-related integrated marketing communication tools for sustainability upon buyers’ buying decisions. The object of the research is promotion-related IMC tools for sustainability. The subject of the research is the influence of product promotion tools for sustainability upon buyers’ buying decisions. Methodology/methods: The research makes use of the results of the studies of food retail chains conducted by the authors in 2017 and 2018. The survey of buyers is based on the results of the survey of leading marketing specialists of food retail chains in 2017. Drawing on the conclusions the authors surveyed randomly selected buyers of Latvian food retail chains with a sample of 1,003 respondents. In order to attain the goal and objectives, the following quantitative and qualitative methods of economic research were used: survey, comparison, grouping, evaluation, market investigation, comparative analysis. The study is based on scientific papers published by Latvian and foreign scholars, general and special literature, and periodicals. The survey data were processed and analysed using the SPSS 23 software. Findings: The research confirmed the hypothesis that the use of integrated marketing communications for sustainability in product promotion enhances consumer awareness of sustainability. The results of the research are of both theoretical and practical value.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; sustainable development; sustainable marketing; integrated marketing communications for sustainability; buyer survey